IMPLEMENTATION OF APPROACHES TO INNOVATION MANAGEMENT OF PUBLIC ADMINISTRATIONS INTO INDUSTRIAL COMPANIES. THEORETICAL CONSIDERATIONS AND MODEL FOR PRACTICAL REALIZATION - Mazelle, Max (European Scientific Journal, ESJ, 2014)
At the beginning the article focuses on general thematic considerations und explains why the implementation of approaches towards innovation management of public administrations into the private sector can be regarded as a reasonable aim. Furthermore, the underlying basic hypotheses are being established. Afterwards, the individual steps of a generally applicable implementation model will be described in detail and additional considerations on implementations and instructions on the course of action will be provided. At the end of each process that has been realized this way, a structured evaluation of the implemented methods and actions will be conducted. On the basis of a specific instruction on the course of action the article describes a generally usable model with the necessary work stages, instruments and required accompanying measures.